Out of Place An Autoethnography of Postcolonial Citizenship - Davids, Nuraan (African Minds, 2022)
Out of Placeoffers an in-depth exploration of Nuraan Davids' experience as a Muslim 'coloured' woman, traversing a post-apartheid space. It centres on and explores a number of themes, which include her challenges not only as a South African citizen, and within her faith community, but as an academic citizen at a historically white university. The book is her story, an autoethnography, her reparation. By embarking on an auto-ethnography, she not only tries to change the way her story has been told by others, transforms her 'sense of what it means to live' (Bhabha, 1994). She is driven by a postcolonial appeal, which insists that if she seeks to imprint her own way of life into the discourses which pervade the world around her, then she can no longer allow herself to be spoken on behalf of or to be subjugated into the hegemonies of others. The main argument of Out of Placeis that Muslim, 'coloured' women are subjected to layers of scrutiny and prejudices, which have yet to be confronted. What we know about Muslim 'coloured' women has been shaped by preconceived notions of 'otherness', and attached to a meta-narrative of 'oppression and backwardness'. By centring and using her lived experiences, the author takes readers on a journey of what it is like to be seen in terms of race, gender and religion - not only within the public sphere of her professional identities, but within the private sphere of her faith community